2012
DOI: 10.1186/1556-276x-7-688
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of dye adsorption time and film thickness for efficient ZnO dye-sensitized solar cells with high at-rest stability

Abstract: Photoelectrodes for dye-sensitized solar cells were fabricated using commercially available zinc oxide (ZnO) nanoparticles and sensitized with the dye N719. This study systematically investigates the effects of two fabrication factors: the ZnO film thickness and the dye adsorption time. Results show that these two fabrication factors must be optimized simultaneously to obtain efficient ZnO/N719-based cells. Different film thicknesses require different dye adsorption times for optimal cell performance. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…6(a and b) respectively. This may be inferred that Jsc is considered as an efficiency-determining parameter since the film thicknesses have shown stronger effect on Jsc than on the other photovoltaic parameters [28][29][30]. Finally, Fig.…”
Section: Ffmentioning
confidence: 75%
“…6(a and b) respectively. This may be inferred that Jsc is considered as an efficiency-determining parameter since the film thicknesses have shown stronger effect on Jsc than on the other photovoltaic parameters [28][29][30]. Finally, Fig.…”
Section: Ffmentioning
confidence: 75%
“…For example, suitable electrolyte and dye materials need to be developed, and the fabrication parameters and design of the nanostructure need to be optimized, which is essential for maximizing the energy conversion efficiency (Kakiuchi et al, 2006;Rao and Dutta, 2008). The effect of the morphology, thickness and presence of aggregates of nanostructured ZnO films on the efficiency of dye-sensitized solar cells was studied by Giannouli and Spiliopoulou (2012) while Chang et al (2012) reported the optimization of dye adsorption time and film thickness for efficient ZnO dye-sensitized solar cells with high at-rest stability.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the photoanodes (in m) for the current ZnO based DSSCs showed a significant increase in the photonto-electric power conversion efficiency. The thickness of the photoanode layers was calculated to be 10.57 m, 16.11 m, and 25.40 m for samples A, B, and C, respectively, by using 3 micromolars per centimeter square and the calculations were performed as per the method given in the literature [35][36][37]. The coating of another material over the parent ZnO leads to increase in the thickness of the coating.…”
Section: Photovoltaic Performances Of Hybrid Zno Based Dsscsmentioning
confidence: 99%